IMPULSE–SLIDING REGIMES IN SYSTEMS WITH DELAY - Alexander N. Sesekin; Natalya I. Zhelonkina (Ural Mathematical Journal, 2016)
The paper is devoted to the formalization of a concept of impulse-sliding regimes generated by positional impulse controls for systems with delay. We define the notion of impulse-sliding trajectory as a limit of a sequence of Euler polygonal lines generated by a discrete approximation of the impulse position control. The equations describing the trajectory of impulse-sliding regime are received.